COMPREHENSIVE REVIEW IN ANALYZING THE EFFECTIVENESS OF NONCHEMICAL PAIN MANAGEMENT METHODS IN ADOLESCENTS. - Mashael Muflih Alqahtani, Eman Mufadhi Alanazi, Hanadi Shafi Alsubaie, Shahad Abdullah Alkhtine, Mansour Ayed Alanezi, Mansour Hamad I Albnayah, Amani Nasser Alotaibi, (Chelonian Research Foundation, 2022)
Pain management in teenagers is a significant part of pediatric medicine and impacts various areas of life, i.e., the body, emotions, and interactions with society. Nonchemical pain management strategies are not chemical interventions; thus, they are substitutes for the pharmaceutical approaches often used to treat pain in adolescents, offering multiple routes for teenagers to minimize pain and enhance their quality. We have conducted a coherent assessment of the performance of nonchemical remedies for teen pain. We submitted various modalities, including physical therapy, cognitive-behavioral therapy (CBT), mindfulness-based interventions, and complementary therapies, in our review. Using an in-depth analysis of the existing literature, I evaluate different studies around chemical-free pain management methods. I also explore the mechanisms behind its action and move on to practical aspects for its adoption in clinics. These should serve as proof of integrating nonchemical pain healing approaches with multidisciplinary care for adolescents and identify research gaps and possible future areas of more profound research. Keywords: nonchemical pain, physical rehabilitation, cognitive-behavioral therapy, mindfulness, and complementary therapies.